Tagasaste (Chamaecytisus palmensis) leaf supplementation to enhance nutrient intake and production performance of sheep in the Ethiopian highlands - Mengesha, M.; Bezabih, Melkamu; Mekonnen, Kindu; Adie, Aberra; Duncan, Alan J.; Thorne, Peter J.; Tolera, Adugna (Springer, 2017)
The objective of this study was to determine the effect of supplementing increasing levels of dried tagasaste (Chamaecytisus palmensis) leaf on the nutrition and performance of sheep fed a basal diet of barley straw. The study had four treatments, which involved supplementation of dried tagasaste leaf at 100, 200, 300, and 400 g/day. Twenty-four yearling Menz sheep (weight 17 ± 0.83 kg) were assigned to one of the four treatments in a randomized complete block design. The experiment comprised a feeding trial lasting for 90 days, a digestibility trial, and carcass evaluation using all animals. Samples of the feed consumed, refused, and feces were analyzed for nutrients. Intake and digestibility of dry matter (DM) and nutrients increased linearly (P < 0.001) as tagasaste supplementation increased from 100 to 400 g/day. Similarly, average daily body weight gain increased linearly (P < 0.001) from 20 to 73 g/day, feed conversion efficiency from 0.04 to 0.10, and dressing percentage from 40 to 48%, as the supplementation increased from 100 to 400 g/day. Proportion of tagasaste leaf in the diet increased from 20 to 50%, while the ratio of neutral detergent fiber (NDF) to crude protein (CP) decreased from 7.9 to 5.3, as the level of supplementation increased. It was thus concluded that supplementation of dried tagasaste leaf up to 50% of the diet DM, resulting in a NDF:CP ratio of 5.3, produces no deleterious effects on the performance of sheep, and inclusion to this level can be applied for superior growth performance and carcass yield in sheep fed crop residue-based diets.